The Performance of Banks in the MENA Region During the Global Financial Crisis - Guglielmo Maria Caporale; Suman Lodh; Monomita Nandy (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper examines the impact of the global financial crisis on the banking sector in the Middle East and North Africa (MENA) region, as well as the main determinants of the profitability of both domestic and foreign banks. The empirical findings suggest that during the crisis the former outperformed the latter in that region. As for the determinants of profitability, size does not appear to play a role, whilst the liquidity ratio and net interest revenues seem to have a negative and positive effect respectively; GDP has a positive effect in the case of domestic banks.
Keywords: G21; 330; MENA region; banking sector; profitability; global financial crisis